Fallow Weed Control with Liberty and Enlist One Tank Mixtures and Application Timings - R. S. Currie; P. W. Geier (Kansas Agricultural Experiment Station Research Reports, 2021)
This study evaluated Liberty (glufosinate) and Enlist One (2,4-D choline) at three application timings and with various tank mix partners for weed control in fallow. Most herbicides tested controlled 94% or more of volunteer sorghum 17 days after the late postemergence treatments in the season. Conversely, Palmer amaranth and crabgrass control was less than 90% with most herbicides. However, control of these species was good when Tricor, or Zidua plus OpTill were applied preemergence followed by Liberty or Liberty and Enlist One late postemergence.
Keywords: Herbicide resistance; sequential applications